Self-murder and self-murderers in social representations of young Russians: An exploratory study - Dvoryanchikov, Nikolay; Bovina, Inna; Vikhristuck, Olesya; Berezina, Elizaveta; Bannikov, Gennady; Konopleva, Inga (Psichologija, 2014)
Premature death caused by self-murder is one of the most serious problems of public health in the world. About one million people disappear for this reason each year, and the further estimations are quite pessimistic. There are no doubts that the current situation is extremely serious and complex; as a result, the importance of the further development and realization of the preventive measures is obvious. Each preventive program in the field of public health should be based on the results of social psychological studies concerning the problem. In the presented paper, we discuss the results of the exploratory study based on the ideas of the social representations theory. The objective of the exploratory study was to analyze the specificity of the social representations of self-murder and self-murderers in two groups of young Russians. A total of 106 subjects (67 females and 39 males) aged 18 to 35 participated in the study. It was supposed that the social representation of self-murder and of self-murderers would be less shared in the group of subjects who have friends or acquaintances among people with self-murder experience (committed self-murder or attempted it); it means that the structure of the social representations would be more complex (the central system would be composed of more elements that correspond to different themes on self-murder), whereas, the social representation of self-murder and of self-murderers in the group of subjects who have no friends or acquaintances with self-murder experience (committed self-murder or attempted it) would be more shared (the central system would consist of less themes) and less complex. The different themes that form the social representations of self-murder and of self-murderers in two groups were revealed. The suppositions got empirical support.